2021
DOI: 10.1093/cvr/cvab043
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning the cardiac O-GlcNAcylation regulatory enzymes governs the functional and structural phenotype of the diabetic heart

Abstract: Aims The glucose-driven enzymatic modification of myocardial proteins by the sugar moiety, β-N-acetylglucosamine (O-GlcNAc), is increased in pre-clinical models of diabetes, implicating protein O-GlcNAc modification in diabetes-induced heart failure. Our aim was to specifically examine cardiac manipulation of the two regulatory enzymes of this process on the cardiac phenotype, in the presence and absence of diabetes, utilising cardiac-targeted recombinant-adeno-associated viral-vector-6 (rAAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 47 publications
3
73
0
Order By: Relevance
“…In DM, glucose may be favoured to be metabolised through alternative pathways such as the HBP due to impairments in insulin signaling, leading to elevated concentrations of UDP-GlcNAc in diabetic mice (Clark et al, 2003). This increase in UDP-GlcNAc production causes an elevation in O-GlcNAc modifications on proteins, as has been observed in left ventricular and right atrial appendage samples from diabetic patients (Prakoso et al, 2021).…”
Section: O-glcnacylation In Diabetesmentioning
confidence: 87%
“…In DM, glucose may be favoured to be metabolised through alternative pathways such as the HBP due to impairments in insulin signaling, leading to elevated concentrations of UDP-GlcNAc in diabetic mice (Clark et al, 2003). This increase in UDP-GlcNAc production causes an elevation in O-GlcNAc modifications on proteins, as has been observed in left ventricular and right atrial appendage samples from diabetic patients (Prakoso et al, 2021).…”
Section: O-glcnacylation In Diabetesmentioning
confidence: 87%
“…The diabetic heart is characterized by increased left ventricular stiffness due to the accumulation of collagen and AGEs 115,116 . Recently, Prakoso et al 50 demonstrated that overexpression of OGT in non‐diabetic mice was sufficient to impair left ventricular diastolic function and increase cardiac interstitial and perivascular collagen deposition, replicating the cardiac phenotype of diabetes. Increased deposition of interstitial extracellular matrix which results in fibrosis in the diabetic heart has been associated with an increase in fibroblast proliferation 117‐119 .…”
Section: Impact Of O‐glcnacylation On Other Cell Types Within the Heartmentioning
confidence: 99%
“…The BMP7 construct, previously utilised in skeletal muscle (Winbanks et al, 2013), was cloned into an rAAV6 expression plasmid consisting of a cytomegalovirus (CMV) promoter/ enhancer packaged into pseudotype-6 capsids (rAAV6), as previously described (Gregorevic et al, 2004;Winbanks et al, 2013;Prakoso et al, 2017;Prakoso et al, 2020;Prakoso et al, 2021a). The purified vector preparations were titered with a customised sequence-specific quantitative PCR-based reaction.…”
Section: Adeno-associated Virus Generation and Administrationmentioning
confidence: 99%